PENGARUH COST OF CAPITAL, FINANCIAL PERFORMANCE, DAN BOARD GENDER DIVERSITY TERHADAP COMPANY VALUE : THE EFFECT OF COST OF CAPITAL, FINANCIAL PERFORMANCE, AND BOARD GENDER DIVERSITY ON COMPANY VALUE - Angela, Aurora; Meilyani, Meilyani (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2024)
Increasing company value is a corporation’s long-term objective. Good capital cost management, optimizing financial performance, and it is anticipated that increasing the number of women on the board of directors will raise the value of the company. Research was conducted to ascertain the impact of cost of capital (coc), financial performance, and board gender diversity on company value. All manufacturing enterprises registered on the Indonesia Stock Exchange in 2020–2022 make up the study's population. There was a purposeful sampling to get the study's sample. Multiple linear regression is used in this study to evaluate the hypothesis. The results found that cost of capital, financial performance, and board gender diversity have an influence on company value. Therefore, companies must manage and pay attention to the cost of capital, financial performance, and gender diversity in the board of directors to increase company value. The contribution of this research is to provide a comprehensive understanding for investors, managers, and policymakers in companies to understand the importance of coc, financial performance, and gender diversity in increasing company value, so that it can be used as a reference for companies in decision making.